Detection of qnrS and tetA resistance coding genes in Pseudomonas aeruginosaof egg-laying hens farmin Cianjur Regency, West Java - FAUZAN ARISANDI; SAFIKA . SAFIKA; FACHRIYAN HASMI PASARIBU (Jurnal Natural, 2021)
The use of antibiotics is an alternative to reduce disease incidence and is used to increase egg-laying hens. This study aims to detect the presence of antibiotic resistance to resistance coding genes in Pseudomonas aeruginosa bacteria. The cloacal swab samples were collected randomly as many 66 samples from several egg-laying hens farms in Cianjur Regency, West Java. The collected isolates were examined bacteriologically. The results of the antibiotic sensitivity test of 8 samples (12.1%) of the Pseudomonas aeruginosa showed the resistance level of antibiotics class tetracycline (tetracycline50%, oxytetracycline75%, and doxycycline50%), fluoroquinolone (enrofloxacin 12.5%), and phenicol (chloramphenicol 12.5%). Pseudomonas aeruginosa was resistant to tetracyclines, oxytetracyclines, doxycycline, enrofloxacin and is sensitive to chloramphenicol. The detection of resistance coding genes showed the genes amount of tetA (62.5%) and qnrS (75%). Efforts to determine the level of resistance and use of antibiotics in farms need regular surveillance and monitoring to ensure the wise use of antibiotics.